2020
DOI: 10.2196/16018
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Rater and Inter-Rater Reliability of Tongue Coating Diagnosis in Traditional Chinese Medicine Using Smartphones: Quasi-Delphi Study

Abstract: Background There is a growing trend in the use of mobile health (mHealth) technologies in traditional Chinese medicine (TCM) and telemedicine, especially during the coronavirus disease (COVID-19) outbreak. Tongue diagnosis is an important component of TCM, but also plays a role in Western medicine, for example in dermatology. However, the procedure of obtaining tongue images has not been standardized and the reliability of tongue diagnosis by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Other methods, for example artificial intelligence (AI) tongue diagnosis, still have barriers for clinical utilization. 23 In our study, we found that CRC patients with metastatic disease had higher TCM-SDS score than those in early stage. Although patients with advanced disease usually had higher symptom burden, whether TCM-SDS score could predict survival outcomes still needs further evaluation.…”
Section: Discussionsupporting
confidence: 49%
“…Other methods, for example artificial intelligence (AI) tongue diagnosis, still have barriers for clinical utilization. 23 In our study, we found that CRC patients with metastatic disease had higher TCM-SDS score than those in early stage. Although patients with advanced disease usually had higher symptom burden, whether TCM-SDS score could predict survival outcomes still needs further evaluation.…”
Section: Discussionsupporting
confidence: 49%
“…Inter-agreements between the ATDS and TCM doctors, as well as among the TCM doctors are both moderate. Intra-rater agree- ment between direct subject tongue inspection and objective tongue image inspection was good (Cohen κ range 0.69-1.0) [5].…”
Section: Present: Objective and Quantitative Tongue Inspection With Modern Tongue Diagnosis Equipment Standalone Systemmentioning
confidence: 88%
“…However, the intervention evaluated by pragmatic trials are often programs requiring flexibility, and the reproducibility is scrutinized (1). Although an unrestricted replicate of the real-world practice best produces evidence on effectiveness for implementation, the protocol may neither be applicable to nor reproducible in other clinical settings as high-quality standardized diagnostic instruments are lacking (50)(51)(52). For instance, the CM symptom-based diagnosis and personalized treatment in diabetes involves subjective professional judgment and likely differs between CM physicians.…”
Section: Strategies To Maximize Reproducibility and Internal Validity In Pragmatic Trialsmentioning
confidence: 99%